The Camping Climate Index (CCI): The development, validation, and application of a camping-sector tourism climate index. (October 2020) - Ma, Siyao; Craig, Christopher A.; Feng, Song
Abstract: Camping is a nature-based tourism activity where individuals spend one or more night away from home in an outdoor setting. Inherent in the definition are time and space, as well as exposure to natural elements such as weather or extremes. This study introduces the novel Camping Climate Index (CCI) to explore the impacts of weather and climatic variability on camping occupancy and optimal camping conditions. Daily meteorological data for 29 for-profit camping locations is analyzed and matched with daily camping occupancy data for the tent, recreational vehicle, and cabin categories. The CCI is empirically validated for camping behaviors compared to other tourism indices including the Tourism Climate Index and Holiday Climate Index. This study is the first to create an index using observed camping occupancy data for the three categories of camping matched with daily weather data that also captures the overriding effects of extreme/adverse weather events. Highlights: The Camping Climate Index (CCI) was introduced, validated, and applied using observed camping and weather data. The CCI addressed a gap in the literature by providing a camping-sector climate tourism index. The CCI was validated against the Tourism Climate Index, the Holiday Climate Index, and an optimization approach. Ideal camping conditions improved from 1997 to 2017 for five of seven climate zones in the study by up to 32 days a year. Seasonality shifts in ideal camping days for 29 camping locations in seven climate zones from 1997 to 2017 was observed.